Trends in Ethical Complaints Leading to Professional Counseling Licensing Boards Disciplinary Actions. (9th January 2019) - Wilkinson, Tyler; Smith, Dannielle; Wimberly, Ramona
Abstract : This article presents findings of a content analysis of the types of ethical violations that led to disciplinary actions ( N = 936) across state counseling licensing boards for professional counselors during the time frame of 2010 to 2014. The most frequent types of ethical violations included failure to acquire the appropriate amount of continuing education, dual relationships (sexual and nonsexual), and misrepresentation of credentials. Implications of the findings and future research needs are discussed.